INFLUENCE OF PRODUCT AND DIGITAL MARKETING ON PURCHASE DECISIONS: THE MEDIATING ROLE OF CONSUMER SATISFACTION : (CASE STUDY OF KAMPUNG LELE KEDIRI) - endah, Endah Kurnia; Novia Ayuanti, Rafikhein (PERFORMA, 2024)
Abstract:This study examines the influence of product quality and digital marketing on purchasing decisions with consumer satisfaction as an intervening variable in Kampung Lele Kediri. The research employs a quantitative approach with a sample of 100 consumers, selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS software. The results reveal several unique findings that contradict previous research. While product quality shows a positive and significant effect on consumer satisfaction (T-statistic 5.417, P-value 0.000, coefficient 0.463), it unexpectedly demonstrates a negative significant impact on purchasing decisions (T-statistic 3.292, P-value 0.001, coefficient - 0.257). Digital marketing efforts prove ineffective, showing no significant influence on either consumer satisfaction (T-statistic 0.890, P-value 0.374) or purchasing decisions (T-statistic 0.057, P-value 0.954). Notably, consumer satisfaction exhibits a negative significant effect on purchasing decisions (T-statistic 3.556, P-value 0.000, coefficient -0.344), contradicting established consumer behavior theories. Furthermore, consumer satisfaction fails to effectively mediate the relationship between product quality, digital marketing, and purchasing decisions. These findings suggest a distinctive consumer behavior pattern in Kampung Lele Kediri, where traditional market dynamics and local consumer preferences may play a more significant role than conventional marketing principles. The study recommends a comprehensive review of pricing strategies, product development approaches, and digital marketing implementation to better align with local market characteristics